2007
DOI: 10.1089/apc.2006.0205
|View full text |Cite
|
Sign up to set email alerts
|

Retention Challenges for a Community-Based HIV Primary Care Clinic and Implications for Intervention

Abstract: The present study sought to elucidate factors involved in loss to follow-up (LTF) among HIVinfected patients who had been receiving medical care at Fenway Community Health (FCH) located in Boston, Massachusetts. FCH provided care to 1143 HIV-infected patients in 2005, predominantly Caucasian men who have sex with men (MSM). Two approaches were used to address the research question. First, 495 patients were identified that had been LTF from [2001][2002][2003][2004][2005]. One hundred seventy-nine eligible patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
27
1
5

Year Published

2008
2008
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 19 publications
4
27
1
5
Order By: Relevance
“…The RWP provides funding for the care of uninsured and underinsured PLWH and mandates improvements in the quality of care for PLWH. 6,9,25 In previous studies, uninsured PLWH were less likely to meet HIV-specific measures (retention in care, use of ART, and virologic suppression), [35][36][37][38][39][40][41] and nonprivate insurance was associated with more barriers to care. 42 It would therefore be expected that uninsured PLWH may meet fewer performance measures.…”
Section: Discussionmentioning
confidence: 99%
“…The RWP provides funding for the care of uninsured and underinsured PLWH and mandates improvements in the quality of care for PLWH. 6,9,25 In previous studies, uninsured PLWH were less likely to meet HIV-specific measures (retention in care, use of ART, and virologic suppression), [35][36][37][38][39][40][41] and nonprivate insurance was associated with more barriers to care. 42 It would therefore be expected that uninsured PLWH may meet fewer performance measures.…”
Section: Discussionmentioning
confidence: 99%
“…These differences were not explained by significant variations in definitions of LFU, as the majority defined LFU as patients who had not been seen in a clinic for at least 12 months [22-24,26-28]. …”
Section: Discussionmentioning
confidence: 99%
“…Some patients simply fail to enter outpatient care after diagnosis [13]. Others enter care but are unable to be engaged and retained in regular HIV medical care [14,15]. Others have comorbidities such as mental illness and substance abuse that severely limit their ability to access and remain in medical care.…”
Section: What Is the Problem?mentioning
confidence: 99%
“…More pressing basic subsistence needs such as food, clothing, housing, childcare or transportation, may compete with medical care priorities [16]. As alluded to above, lack of insurance (or type of insurance) presents a barrier to care and multiple studies have shown this [15,17,18]. Reasons for delays in care have been elucidated from the HIV Cost and Services Utilization Study (HCSUS), which surveyed a national probability sample.…”
Section: What Is the Problem?mentioning
confidence: 99%
See 1 more Smart Citation